A problemática da fixação do valor da reparação por dano moral: um estudo sobre os requisitos adotados pela doutrina e jurisprudência tendo em vista a natureza e a função pedagógico-punitiva do instituto - Santos, Maria de Fátima Zanetti Barbosa e (2008)
This piece of work has the intent of making a critical rereading of the requisites adopted by the major part of the doctrine and jurisprudence on fixation of the value for reparation when it comes to punitive damages. An analysis of those requisites was made with the purpose of showing that some of them are obsolete due to the arrival ofthe Federal Constitution in 1988 and that others should have their application restricted to the repairing of punitive damages, since their origin is and they are connected in the matter ofvalue to the restitutory Law. From the analysis conducted, we conclude that: can not be applied requisites that taper with the restitutory Law; that the punitive damages' purpose protects superior value of alI society' s interest that superposes the material values; that the parts find themselves in situation of inequity when it comes to work contract; that work is essential good for workers and the entire society; and that is why specific requisites are a necessity, as well as the application of the punitive-pedagogic aspect, reaching the prohibitive function of the Law, which, materializes through significant values for reparation